HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DAN KOORDINASI MATA TANGAN DENGAN HASIL FREE THROW PADA CLUB BOLA BASKET PUTRI YOUNG LADIES PEKANBARU - Ramadania Ramadania; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This reserch is intendedto see the correlation of elasticity of wrist and hand-eye coordination with the result of free throw on women basket ball club, Young Ladies Pekanbaru. The purpouse of this research also to train member, so they can do free throw with good method. With Young Ladies Club as the population , sample in this research is all population that contain 12 members. Instrument that has beed used in this research is elasticity test of wrist, throw and catch tennis ball, and free throw test, to measure shooting skill when doing free throw. After that, data counted with statistic, to examine normality with lilofors test onsignificant level of a (0,05). The Hypothesis of this research shows there is correlation of elasticityof wrist and hand-eye coordination with free throw result. As the result of this research with statistic procedure, researcher finds conclution that is correlation about elasticity of wrist and hand-eye coordination with free throw results, with calculating result the correlation of elasticity of wrist with free throw skill is rhitung (0,91) > rtab(0, 4973), correlation of hand-eye coordination with free throw rhitung (0,82) > rtab(0,4973) and correlation of elasticity of wrist and hand eye coordination with free throw skill is Rhitung (0,96) > rtab(0,4973).Key Words: Wrist Flexibility and Hand-Eye Coordination, Free Throw.